ANALYSIS OF THE INFLUENCE OF THE NUMBER OF STUDENTS AND TOURISTS ON THE ROOM OCCUPANCY RATE IN BALI - I Made Krisna Adi Chandra; Tasya Winston; I Putu David Adi Saputra (Bajang Institute, 2025)
Tourism is a key sector in Bali's economy, with industry growth influenced by various factors, including the presence of tourism students. This research aims to analyze the correlation between the number of tourism students and the level of tourist visits and room occupancy in Bali's tourist destinations. The method used is secondary data analysis from various relevant sources, including tourism statistics, higher education data, and hospitality industry reports. The results show that the number of tourists is the most influential variable on room occupancy rates, whereas the number of students does not show a significant effect on either occupancy or the number of tourists. These findings emphasize that in the context of destination management like Bali, tourism activities remain the main driver of the accommodation industry, not educational activities. This research provides important insights for strengthening sustainable tourism strategies while still considering the synergy between the education sector and the tourism industry